No Man's Land: Mythology of War, Masculinity and Homeland in Greek and Serbian Aftermath Cinema - Carr, Rebecca Ann (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of German, 2021)
This thesis explores the dynamic between cultural mythology and trauma in aftermath cinema. After a society has experienced a significant disturbance, it is common to reckon with the stories that tell of its beliefs, traditions, and expectations leading up to the turmoil. Here, the aim is to consider how films portray an ordeal as having irrevocably injured or altered a collective identity. The first section explains how mythology will be operationalised and surveys the predominant theories about trauma at the national level. The second section analyses films produced in the two societies a decade after strife: 1980s Greece and 2010s Serbia. Focusing on the themes of war, masculinity and homeland in the respective countries, an inverse correlation between mythology and trauma emerges. The more a film mythologises conflict, the less it implies the collective identity has been damaged. On the Milky Road (Kusturica 2016, Serbia) depicts the Yugoslav Wars (1991-2001) as another chapter in Serbia?s mythology of a ?heavenly people? under siege. In contrast, A Serbian Film (Spasojević 2011, Serbia) shows myths of Balkanisation to be exploitative and traumatic. Voyage to Cythera (Angelopoulos 1984, Greece) is a contemplative critique of Greece?s struggle to discuss the myths and reality of the Greek Civil War (1946-1949) which was prolonged by the Colonels? Junta (1967-1974). The Stone Years (Voulgaris 1985, Greece) condemns the officially sanctioned corrupt mythology imposed from 1946-1974 for the havoc it wreaked on the lives of Greek communists. The conclusion considers Greece?s subsequent and Serbia?s contemporary cinematic trends to see how they engage with other social issues. Lastly, this thesis argues that film is a viable local alternative to the universal method of standardising national memory.
APPROVED
Keywords: Trauma; Film; Mythology; War; Masculinity; Homeland